Glioma Stem Cells but Not Bulk Glioma Cells Upregulate IL-6 Secretion in Microglia/Brain Macrophages via Toll-like Receptor 4 Signaling. Issue 5 (May 2016) - a Dzaye, Omar Dildar; Hu, Feng; Derkow, Katja; Haage, Verena; Euskirchen, Philipp; Harms, Christoph; Lehnardt, Seija; Synowitz, Michael; Wolf, Susanne A.; Kettenmann, Helmut
Abstract : Peripheral macrophages and resident microglia constitute the dominant glioma-infiltrating cells. The tumor induces an immunosuppressive and tumor-supportive phenotype in these glioma-associated microglia/brain macrophages (GAMs). A subpopulation of glioma cells acts as glioma stem cells (GSCs). We explored the interaction between GSCs and GAMs. Using CD133 as a marker of stemness, we enriched for or deprived the mouse glioma cell line GL261 of GSCs by fluorescence-activated cell sorting (FACS). Over the same period of time, 100 CD133 +  GSCs had the capacity to form a tumor of comparable size to the ones formed by 10, 000 CD133 - GL261 cells. In IL-6 -/- mice, only tumors formed by CD133 +  cells were smaller compared with wild type. After stimulation of primary cultured microglia with medium from CD133-enriched GL261 glioma cells, we observed an selective upregulation in microglial IL-6 secretion dependent on Toll-like receptor (TLR) 4. Our results show that GSCs, but not the bulk glioma cells, initiate microglial IL-6 secretion via TLR4 signaling and that IL-6 regulates glioma growth by supporting GSCs. Using human glioma tissue, we could confirm the finding that GAMs are the major source of IL-6 in the tumor context.